Reframing the Role of Spirituality in Social Entrepreneurship: A Conceptualization of the Social Enterprise Spirituality Perspective (SESP) - Ronny Ersya Novianto Putra; Hempri Suyatna; Dian Utami Ikhwaningrum; Desy Ayu Nining Dwi Rahmawati (Universitas Tribhuwana Tungga Dewi, 2026)
Although social enterprises are estimated to exceed 10 million organizations worldwide, generating approximately USD 2 trillion in annual economic value (Schwab Foundation World Economic Forum, 2024), research on their sustainability remains predominantly grounded in economic and institutional perspectives. Previous studies have largely conceptualized spirituality as an individual attribute or a normative organizational value, providing limited explanation of how spirituality functions as an institutional mechanism that shapes social enterprise sustainability. Addressing this gap, this study develops the Social Enterprise Spirituality Perspective (SESP) framework to conceptualize spirituality as an embedded institutional logic that mediates the tensions between market and social logics. The research employs a qualitative multi-site case study involving four community-based social enterprises in Indonesia, complemented by a systematic literature review of Scopus- and Web of Science-indexed publications from 2014–2024. Data were analyzed using thematic synthesis. The findings reveal that spiritual embeddedness operates through three core mechanisms: normative binding force, meaning-making system, and behavioral regulator. The novelty of this study lies in the development of spiritual embeddedness as an observable and empirically operationalizable organizational mechanism. Theoretically, SESP extends the institutional logics perspective by integrating the spiritual dimension into social entrepreneurship scholarship and provides a conceptual foundation for future studies on social enterprise sustainability, particularly in developing-country contexts.Meskipun social enterprise global diperkirakan mencapai lebih dari 10 juta organisasi dengan kontribusi ekonomi sekitar USD 2 triliun per tahun (Schwab Foundation World Economic Forum, 2024), kajian mengenai keberlanjutannya masih didominasi perspektif ekonomi dan kelembagaan. Penelitian terdahulu cenderung memosisikan spiritualitas sebagai atribut individual atau nilai normatif organisasi, sehingga belum menjelaskan bagaimana spiritualitas bekerja sebagai mekanisme kelembagaan yang memengaruhi keberlanjutan social enterprise. Berangkat dari kesenjangan tersebut, penelitian ini mengembangkan kerangka Social Enterprise Spirituality Perspective (SESP) untuk menjelaskan spiritualitas sebagai embedded institutional logic yang menjembatani ketegangan antara logika pasar dan logika sosial. Penelitian menggunakan pendekatan kualitatif melalui studi kasus multi-situs pada empat social enterprise berbasis komunitas di Indonesia, yang dipadukan dengan systematic literature review terhadap artikel terindeks Scopus dan Web of Science periode 2014–2024. Data dianalisis menggunakan thematic synthesis. Temuan menunjukkan bahwa spiritual embeddedness beroperasi melalui tiga mekanisme utama, yaitu normative binding force, meaning-making system, dan behavioral regulator. Kebaruan penelitian ini terletak pada pengembangan konsep spiritual embeddedness sebagai mekanisme organisasi yang dapat diamati dan dioperasionalkan secara empiris. Secara teoretis, SESP memperluas perspektif institutional logics dengan mengintegrasikan dimensi spiritual ke dalam studi kewirausahaan sosial serta menyediakan landasan konseptual bagi penelitian keberlanjutan social enterprise di negara berkembang.